Elastic substrates for stretchable devices - Leow, Wan Ru (2017)
Stretchable devices, with the capability of retaining their functionalities under stretching, are drawing much attention as a promising solution to address the mechanical mismatch between traditional stiff electronics and soft curvilinear biological systems. Intensive efforts have been made toward the advancement of stretchable devices, such as the development of novel mechanically durable materials, deformable conductors and circuits, novel processing methods, and elastic matrixes for stretchable substrates and system integration. Among these, the elastic substrate constitutes the component that bears the applied strain and thus endows the device with stretchability, rendering its properties crucial to the overall performance of stretchable devices. This article provides a summary of the elastic materials commonly employed as stretchable substrates, as well as reveals fundamental insights into the properties requirements in the selection of stretchable substrates. Important challenges and strategies in the development of elastic matrices for stretchable devices are also discussed.